Parental support and exclusive breastfeeding at 3 months in West Java, Indonesia: a mixed-methods approach - Ratu Ayu, Dewi Sartika; Fadila, Wirawan; Wawan, Gunawan; Primasti, Nuryandari Putri; Mohd Shukri, Nurul Husna (Korean Pediatric Society, 2024)
Background The exclusive breastfeeding (EBF) rate in Indonesia is lower than expected. Among the key factors affecting breastfeeding practices, paternal support has been suggested.